Risk management level determinants in Visegrad countries – sectoral analysis - Belas, Jaroslav; Gavurova, Beata; Kubak, Matus; Novotna, Andrea (Technological and Economic Development of Economy, 2023)
Increasing competition has emphasized the need for creating and using more effective strategies at the level of SMEs to achieve competitive advantage. SMEs face higher risks in terms of the globalization due to the limited resources as well as size. The objective of the study was to examine the determinants of risk management with an emphasis on the sector specifics of SMEs in the V4 countries. This enables the quantification of sectoral differences in relation to the socioeconomic determinants. The research sample included 1585 SMEs from the V4 countries. The data obtained from SME managers and owners were processed using the descriptive statistics and logistic regression. The results of the analyses confirm the existence of differences across SMEs concerning the risk management, which are determined by the country in which a given company operates, industry, gender and age of its manager or the owner of the company. The results of the study provide a valuable platform for the development of systems to measure and assess business risks in companies and to set up training systems. It will also enhance the development of international and national benchmarking indicators and the creation of international databases for comparative analyses.